The Functions of Code-Switching - Chitra Latiffani (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2018)
Code-switching is a phenomenon that happening nowadays in daily conversation that used by teenager and adult. It’s occur not only in conversation, social media and networking but also in printed media. This research attempt to know if there any code-switching that used in an english course, the function and who are the user of it. This research subject consist of 3 students and an english teacher. The data consist of audio-recordings of authentic teacher and student conversation held in the English course. From the result of the research: There is function of code-switching in an English course, the functions of code-switching in an English course are happen to change in situation and the teacher is the most participants who used code-switching in an English course. Keywords: code-switching, language